Humanism and America : an intellectual history of English colonisation, 1500-1625 - Fitzmaurice, Andrew (Ideas in context, 2003)
Humanism and America is the first major study of the impact of Renaissance humanism upon the English colonisation of America. Andrew Fitzmaurice conducts his analysis through an interdisciplinary examination of a broad spectrum of writings, ranging from the works of Thomas More to those of the Virginia Company.